SOCIAL CAPITAL AND AIR POLLUTION: EVIDENCE FROM TURKEY - Cuma Demirtaş; Munise Ilıkkan Özgür (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
This study analyses the impact of social capital on air pollution in all 81 cities of Turkey between 2008 and 2018 via utilizing the panel data method to test for the EKC hypothesis. Within this context, five panel groups are formed, where four of those are formulated vis-à-vis their socioeconomic development levels by taking into account the SEGE report issued by the Ministry of Development. Moreover a city-based social capital index is developed by utilizing the principal component analysis (PCA). Empirical findings show that a U-shaped income-emission relationship is prevalent in Turkey, whereas no significant income-emission interdependency exists within the aforementioned panel groups developed. In addition, it is deduced that population density is a pre-determinant of the rise in air pollution for all panel groups studied, while the hypothesis that social capital index has a significant impact on the latter variable is rejected. It is expected that this work will contribute to the existing literature through its investigation of the impact of social capital index structured via taking into account the cities’ socioeconomic development levels on air pollution. The dataset used has a significant lack of observations for certain cities, so it would be valuable to formulate advanced technical modeling by creating a more complete dataset. Also, various other proxies explaining environmental degradation such as water pollution can be included in the model.